Pengaruh Kontrak Psikologis dan Psychological Well Being Terhadap Keterikatan Kerja - Devy Sofyanty (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Research is aimed to analyze the influence of psychological contract and psychological well being on work enggagement. Methods of research using quantitative methods using purposive techniques. Subjects in this research is employee of PT Tulip Promo Sekawan. Which is 90 person. Measuring instrument used by a psychological contract scale based on the theory of Whyte, psychological well being base on the theory of Ryff and work enggagement base on the theory of Schaufeli dan Bakker. Data were analyzed using multiple linear regression. These result indicate significant relationship between psychological contract, and psychological well being on work engagement. Based on the results of the research, then obtained the following findings: (1) simultaneous psychological contract and psychological well being significant impact on work enggagement (2) partially psychological contract positive and significant impact on work enggagement, (3) partial psychological well being positive and significant effect on work engagement. That is psychological contract and psychological well being can be applied to be a predictor variables to predict work engagement.